‘Making the Invisible Visible’: Legislation on Transboundary Aquifers - Mádl, Miklós Vilmos (Central European Academy Law Review, 2023)
This article addresses an area of international law that is not often discussed, namely, the challenging management of transboundary aquifers. Following a short introduction to the importance and topicality of transboundary aquifers and how universal international law instruments deal with them, this article dives into an analysis of existing bilateral and multilateral cooperations of transboundary aquifers by systematically examining these systems based on the forms of cooperation, their institutional structures, whether they employ quantitative and qualitative measures and how they resolve disputes. Drawing from the experiences of the analysed cooperations, the article proposes a step-by-step path to improve the management of these resources. The article argues that it is possible to successfully prevent wasting resources by invoking the idea of giving more attention to these resources, establishing an international instrument to provide a minimal level of protection to transboundary aquifers and setting up cooperations to manage the given resources.